2003
DOI: 10.1002/adfm.200304404
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State Photovoltaic Thin Films using TiO2, Organic Dyes, and Layer‐by‐Layer Polyelectrolyte Nanocomposites

Abstract: We report photovoltaic devices consisting of patterned TiO2, porphyrin dyes, and layer‐by‐layer (LBL) polyelectrolyte multilayer/oligoethylene glycol dicarboxylic acid (OEGDA) composite films. A composite polyelectrolyte LBL/OEGDA film was fabricated by formation of an alternating multilayer of linear polyethyleneimine (LPEI) and polyacrylic acid (PAA), followed by immersion of the LBL film into an OEGDA aqueous solution. The ionic conductivity attained in this LBL LPEI/PAA and OEGDA composite film was approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
90
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(94 citation statements)
references
References 54 publications
0
90
0
3
Order By: Relevance
“…The incorporation of low molecular weight diacid ethylene oxide derivatives (OEGDA) in acidic water in the presence of LiI salts were found to result in ionic conductivities of 10 ±5 at room humidities. [61] Further investigations have indicated that when fully formed LPEI/PAA films are introduced to the OEGDA/LiI aqueous solution at low pH, the OEGDA is incorporated in large quantities into the interior of the film. It has recently been determined that the high levels of incorporation are due to a transition from a continuous to a nanoporous film morphology due to spinodal decomposition and phase segregation upon protonation of highly charged acid groups at pH 2±3; these transitions, which will be discussed in a following section, were first discovered and investigated by Rubner and co-workers in PAH/PAA thin films.…”
Section: Solid-state Electrolytesmentioning
confidence: 99%
“…The incorporation of low molecular weight diacid ethylene oxide derivatives (OEGDA) in acidic water in the presence of LiI salts were found to result in ionic conductivities of 10 ±5 at room humidities. [61] Further investigations have indicated that when fully formed LPEI/PAA films are introduced to the OEGDA/LiI aqueous solution at low pH, the OEGDA is incorporated in large quantities into the interior of the film. It has recently been determined that the high levels of incorporation are due to a transition from a continuous to a nanoporous film morphology due to spinodal decomposition and phase segregation upon protonation of highly charged acid groups at pH 2±3; these transitions, which will be discussed in a following section, were first discovered and investigated by Rubner and co-workers in PAH/PAA thin films.…”
Section: Solid-state Electrolytesmentioning
confidence: 99%
“…Recently, research of this method has become application-oriented as can be seen in several reports including surface modification for superhydrophobicity [868,869], sensor preparation [870][871][872][873][874], electrochromic devices [875], photochromic devices [876], thin film transistors [877], fuel cells [878], solid-state photovoltaic devices [879], rectifying junctions [880], and chiral switching [881].…”
Section: Layer-by-layer Assemblymentioning
confidence: 99%
“…Hammond and coworkers proposed the use of chemically patterned surfaces produced by stamping techniques as templates for ionic multilayer assembly based on stamping techniques ( figure 103A(a)) [864,865]. The LbL multilayers, as a polyelectrolyte platform, were deposited on a solid support and terminated by using a layer containing an amine group.…”
Section: Layer-by-layer Assemblymentioning
confidence: 99%
“…Благодаря широкому выбору органических материалов с различными свойствами, такие слои оказываются полезными для создания просвет-ляющих покрытий [1], мембран, в качестве функциональных слоев тран-зисторов [2], солнечных элементов [3], запоминающих устройств [4], а также сенсорных структур электролит−диэлектрик−полупроводник [5]. Задача нашего исследования заключается в том, чтобы максимально использовать возможности полупроводникового материала в процессе нанесения на него органических мультислойных покрытий для придания им необходимых свойств и прогнозирования характеристик гибридной структуры в целом.…”
unclassified